KEMISKINAN DALAM MASYARAKAT NELAYAN - Masyuri Imron (LIPI Press, 2003)
Most fishermen live in poverty. They manifest in several dimensions: economic, social culture and politic. It also cover both family poverty and physical infrastructure. Many factors affected fishermen poverty. The first is their traditional gear, and the second is their dependence upon tengkulak (fish trader). In some cases, the existence of TPI (Fish Auction Place) contributes to impoverish them. For labour, this condition especially for labour fishermen make their life more difficult, because of unjustice producion sharingt. To increase their income, developing fishing gear capacity is a necessity. Their dependence upon tengkulak should also be minimized to develop fishermen bargaining position. It is also supported by restructuration of share product system, to be more favorable to labours. It is important to make fishermen as a subject in development. It means that they should be invited to discuss their problem, as well as solutions based on their aspiratio, because development is not only in economic terms, but how to make the poor to be more human.